Toronto :A Play of History (jeu d'histoire) - Dompierre, Louise; Balkind, Alvin; Ferguson, Bruce; Allan, Blaine (Toronto : The Power Plant, 1987)
Shelagh Alexander ; Ian Carr-Harris ; Robin Collyer ; General Idea ; Nancy Johnson ; Liz Magor ; John Massey ; Michael Snow ; Joanne Tod ; Robert Wiens ; Shirley Wiitasalo ; etc.
Toronto : A Play of History (jeu d'histoire), Catalogue to accompany an exhibition held at The Power Plant, Toronto, May 1-June 17, 1987
English
kunstcatalogus
Keywords: Toronto